Preclinical assessment of the neutralizing efficacy of snake antivenoms in Latin America and the Caribbean: A review - Gutiérrez, José María (Toxicon (Oxford), 2018)
The preclinical evaluation of the neutralizing efficacy of antivenoms is mandatory before a product is introduced for clinical use. The World Health Organization (WHO) guidelines for antivenoms categorize the tests used in preclinical studies as ‘essential assay’ (neutralization of lethality) and ‘additional recommended assays’ (neutralization of other relevant toxic activities). The present review presents an overview of the methodological aspects of snake antivenom preclinical efficacy tests, and summarizes the studies performed in this subject on antivenoms used in Latin America and the Caribbean. General trends emerging from this analysis show that: (a) Bothrops antivenoms have a broad spectrum of neutralizing efficacy against venoms of snakes of the genera Agkistrodon, Atropoides, Bothriechis, Bothrops, Cerrophidion, and Porthidium. (b) Crotalus antivenoms show a dichotomic pattern of efficacy depending on whether the venoms used for immunization are crotoxin-rich or metalloproteinase-rich. (c) A complete neutralization of Lachesis sp venoms is achieved only by antivenoms that include Lachesis sp venoms in the immunizing mixture. (d) Micrurus sp venoms have a high immunological heterogeneity which impacts in the cross-neutralization by available antivenoms. There is a need to further expand the knowledge base of the preclinical efficacy of antivenoms in Latin America and the Caribbean. [Display omitted] •The methodologies used for the preclinical evaluation of antivenoms are discussed.•The studies on preclinical evaluation of antivenoms in Latin America are reviewed.•There is a great extent of cross-neutralization between Bothropic antivenoms nad many venoms.•An immunological dichotomy occurs in the venoms of Crotalus sp.•There is a high immunological similarity in the venoms of Lachesis sp.